Effects of Taichi exercise on knee and ankle proprioception among individuals with knee osteoarthritis. Issue 2 (2nd April 2020) - Hu, Xiaoyue; Lai, Zhangqi; Wang, Lin
ABSTRACT: The study aimed to investigate the effects of 24 weeks Taichi intervention on knee and ankle proprioception amongst individuals with knee osteoarthritis (KOA). Ninety-two patients with KOA were included in the current study, involving 52 participants in the intervention group and 40 participants in the control group. The intervention group performed Taichi exercise for 24 weeks, the control group accepted the health education lectures. The main outcome of this study was the proprioception of the knee and ankle which was measured by an electric-driven movable frame. Between- and within-group differences were evaluated through the repeated-measurement ANOVA. For the Taichi group, the differences in the changes in ankle proprioception were significant on ankle plantarflexion (p = 0.03), ankle dorsiflexion (p = 0.043), ankle varus (p = 0.019) and knee flexion (p = 0.01) between the baseline and post-test measures. Twenty-four weeks Taichi exercise may improve the ankle and knee proprioception of patients with KOA.